Seroprevalence of Cryptococcus Sp. Infection Among HIV Patients in a Tertiary Hospital in Ghana (Journal of Science and Technology, 2025)
Introduction: In persons living with HIV, fungal infections contribute significantly to increased morbidity and mortality. Cryptococcal infection is exemplar of invasive opportunistic fungal infections that affect HIV patients. Diagnosis of fungal infections however remains a challenge in Ghana as in many developing countries. Subsequently, there is scanty published literature in Ghana. This can be attributed to the paucity of test assays available for the infection. The purpose of this study was to determine the seroprevalence of the cryptococcal antigen in persons living with HIV in Ghana.Methodology: The study was conducted from August to November, 2018 and included 80 stored serum samples from HIV patients who had reported at the Komfo Anokye Teaching Hospital (KATH), Kumasi, Ghana. Qualitative test was done using the Dynamiker® CrAg Lateral Flow Assay. Results were recorded as positive (++), weakly positive (+) and negative (--). Seroprevalence was also categorized according to patient demographic data as well as HIV treatment statuses.Results: A prevalence of 11.3%was observed, with 9 samples being positive for the antigen and 71 being negative. The study found 10% of patients on ART testing positive, with 13% of ART-naïve samples testing positive for the cryptococcal antigen. There was however no significant association between ART regimen, age or gender and a positive test for the cryptococcal antigen (p=0.05).Conclusion: Approximately 1 in 10 PLWH in this sample had cryptococcal antigenemia, justifying a need for the consideration of routine screening for this invasive fungal disease regardless of antiretroviral treatment status.